Factors that Cause the Monastery and Cetiya under the Auspices of the Pekanbaru MBI PC - Hadion Wijoyo; I Putu Gelgel; Ida Ayu Komang Arniati (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The Indonesian Buddhist Council is one of the Buddhist Religious Councils that was established in 1955. One of the Riau branch administrators is Pekanbaru. Pekanbaru as the capital city of Riau Province houses 7 (seven) Viharas and Cetiyas. Each Vihara and Cetiya has its own problems such as the absence of activities other than Vesak and Kathina Celebrations (Buddhist holidays), including the lack of attention and guidance for administrators and devotees. This study uses a qualitative-analytic method with a religious and cultural approach. The results obtained are as follows. There are several factors that cause service not optimal, such as parking facilities, a service request system that is still manual, the lack of information on Vihara and Cetiya activities, the level of willingness and competence of priests and managers of places of worship that is still lacking. Second, PC MBI Pekanbaru has provided good guidance to Pandita, the manager of the house of worship, in making work plans so that services to the people are maximized, but this requires monitoring and evaluation in its implementation. In addition, PC MBI Pekanbaru has sought to civilize the community where Pekanbaru Buddhists are dominated by the Chinese ethnic group.